Morphology, bedforms and bottom sediments of Mar do Ararapira, southern Brazil - Angulo, Rodolfo José; Souza, Maria Cristina; Sielski, Luiz Henrique; Nogueira, Raissa Araújo; Müller, Marcelo Eduardo José (Quaternary and Environmental Geosciences, 2019)
Mar do Ararapira is an unusual estuary located at the border of Paraná and São Paulo states, in a relevant area of ecological interest and where an opening of a new inlet occurred in August 2018. Differing from classical estuarine models Mar do Ararapira has three inlets, one with open sea and two with the estuarine systems of Baía de Trapandé and Baía dos Pinheiros, the latter through an artificial channel named Canal do Varadouro. Mar do Ararapira also has multiple riverine inputs and the estuary head is not well defined. This paper presents: (a) Mar do Ararapira watershed characteristics, (b) an update of coastline shift close to the inlet and (c) a characterization of the estuarine bathymetry, bottom sediments and bedforms in 2009 and 2011. Comparison of parameters before and after an opening of a new inlet will help both the management of the estuary`s natural resources and the lives of the people inhabiting the surroundings. It is concluded that Mar do Ararapira corresponds to the lower part of an estuary. Its watershed extends 221.6 km2 and is composed by three different morphologic sectors, which drains mountains and coastal plains. It presents a significant fresh-water input, estimated to range from 6.6 to 9.1 m3/s, and weak connectivity with its neighbor estuarine complexes. It is a shallow water body, with a mean depth of 4 m, where a deep main channel suggests intense bottom erosion by tidal currents. The ocean inlet migrates southwestward, mainly under the influence of high energy events. Prevailing bottom sediments are sand and muddy-sand. Subaqueous-sand-dunes and plane-beds are the most common bedforms at Mar do Ararapira. Three estuarine dynamically different sectors were recognized: (a) an inner sector with low tidal-current velocities and finer sediments; (b) a middle sector similar to a fluvial meander in dynamics, with higher tidal-current velocities and sandy sediments, where concave coasts are continuously eroded and convex coasts are silted; and (c) an outer sector, in which tidal-currents are segregated.